FAD2-DGAT2 Genes Coexpressed in Endophytic Aspergillus fumigatus Derived from Tung Oilseeds - Yi-Cun Chen; Yang-Dong Wang; Qin-Qin Cui; Zhi-Yong Zhan (The Scientific World Journal)
Recent efforts to genetically engineer plants that contain fatty acid desaturases to produce valuable fatty acids have made only modest progress. Diacylglycerol acyltransferase 2 (DGAT2), which catalyzes the final step in triacylglycerol (TAG) assembly, might potentially regulate the biosynthesis of desired fatty acids in TAGs. To study the effects of tung tree (Vernicia fordii) vfDGAT2 in channeling the desired fatty acids into TAG, vfDGAT2 combined with the tung tree fatty acid desaturase-2 (vfFAD2) gene was co-introduced into Aspergillus fumigatus, an endophytic fungus isolated from healthy tung oilseed. Two transformants coexpressing vfFAD2 and vfDGAT2 showed a more than 6-fold increase in linoleic acid production compared to the original A. fumigatus strain, while a nearly 2-fold increase was found in the transformant expressing only vfFAD2. Our data suggest that vfDGAT2 plays a pivotal role in promoting linoleic acid accumulation in TAGs. This holds great promise for further genetic engineering aimed at producing valuable fatty acids.